Effect of Echinacea Purpurea Extract on Anxiety-Like Behaviors in Neonatal Rats - Ghorbani Yekta, Batool; Ahmadzadehfar, Noushin Zahra; Yazdanjo, Sepideh (Galen Medical Journal, 2017)
Background: The use of herbal products is increased among people wordwide. Regarding lacking evidence on the use of herbal medication in children, this study was aimed to determine the effects of Echinacea Purpurea extract on anxiety-like behavior in neonatal rats. Materials and Methods: Forty male Wister strain pups in four groups received i.p injections of E. Purpurea extract (40, 80, and 250 mg/kg) or saline on 5th to 9th postnatal days. All pups were examined for anxiety test on the 22nd postnatal day in the elevated plus-maze test. During the test, parameters include percentage of open arm time (%OAT), percentage of open arm entry (%OAE), head dipping, rearing and locomotor activity have been measured. Results: In the present study, administration of 40, 80 and 250mg/kg doses of the E. Purpurea extract revealed a significant decrease in the %OAT compared to saline group (P<0.01). The E. Purpurea extract decreased head dipping parameters (P<0.01) and increased rearing parameters (P<0.01). E. Purpurea did not significantly change the locomotor activity. Conclusions: The results of present study showed that postnatal administration of E. Purpurea extract increases anxiety in neonatal rats comparing to control group. [GMJ.2017;6(1):52-60]